Narrative and numbers: The value of stories of stories in business - Damodaran, Aswath (New York Columbia University press, 2019)
How can a company that has never turned a profit have a multibillion dollar valuation? Why do some start-ups attract large investments while others do not? Aswath Damodaran, finance professor and experienced investor, argues that the power of story drives corporate value, adding substance to numbers and persuading even cautious investors to take risks.